Do Grandparents Contribute to Their Grandchildren's Learning through Shared Leisure Activities? - Rosa Ana Alonso Ruiz; Eva Sanz Arazuri; Magdalena Sáenz de Jubera Ocón; Mª Ángeles Valdemoros San Emeterio; Ana Ponce de León Elizondo (MDPI AG, 2024)
Intergenerational leisure can be a tool to stimulate and reinforce the learning of primary school students. The aim of this study was to examine which leisure activities shared by grandparents and their grandchildren are carried out from the perception of intergenerational learning as one of the main reasons for joint practice, and its link with the grandparents' level of education. An ad hoc questionnaire was administered to 329 students aged 6 to 12 years in the north of Spain, and a descriptive study and inferential analysis of the data were carried out. The leisure activities that students highlight the most as experiences in which they perceive that by sharing them with their grandparents, they learn from them, are board games, artistic activities, caring for plants or gardens and reading. There are only significant differences in the learning perceived by primary school students depending on the level of education of their grandparents in caring for plants or vegetable gardens, as the grandparents of children aged 6 to 12 in the northern part of Spain are more able to teach their grandchildren to care for plants or vegetable gardens when their level of education is primary education. These four activities highlighted by the grandchildren as facilitators of knowledge are very interesting instruments to stimulate and reinforce the education of primary school students, so involving grandparents in their grandchildren's education and taking advantage of their knowledge and experience, as well as their ability to stimulate their grandchildren, is a good strategy to turn free time into valuable leisure time.